(untitled) (Revista Sistemas de Producción Agroecológicos, 2026)
Colombia harbors more than 30 primate species, many threatened or endangered, positioning bioparks as critical actors in species conservation and public environmental education. We report a fatal case in an adult male woolly (churuco) monkey (Lagothrix lagotricha) maintained at Los Ocarros Biopark (Meta, Colombia) that progressed to multiorgan failure. On July 28, 2023, the animal presented inappetence, weakness, and aversion to the handling area. Empirical therapy was initiated with oxytetracycline (20 mg/kg IM q48h) and vitamin B complex (10 µg/ kg IM, single dose). Hematology revealed leukocytosis; serum biochemistry showed elevated ALT and increased BUN/urea, suggestive of azotemia. On August 4, the patient was referred to the University of Los Llanos Veterinary Clinical Center. Under ketamine anesthesia (5 mg/kg IM), echocardiography, thoracic radiography, hematology, and biochemistry were performed, demonstrating cardiomegaly, mild hydropericardium, ventricular hypertrophy, right-sided heart failure with ascites, hepatic congestion, and renal disease compatible with glomerulitis. Physical examination identified a grade 3/6 systolic murmur, and coproparasitology detected Strongylus spp. Management included furosemide (2 mg/kg PO q12h × 5 days), diltiazem (2 mg/kg PO q24h × 5 days), pyrantel pamoate (11 mg/kg PO), and adjunct homeopathic preparations (Trinov, Coenzyme, Ubichinon; 0.3 mL each PO BID). A transient improvement in appetite and behavior was noted on August 8. During physical restraint for follow-up on September 6, the animal developed shock and died suddenly. Necropsy (September 13) documented a markedly enlarged heart ( 60% of thoracic volume) with serosanguineous pericardial effusionmild tricuspid valve deformity, severe coronary congestion, irregular kidneys with poor corticomedullary distinction and partially adherent capsule, and adrenal hemorrhages. Death was attributed to multiorgan failure secondary to right congestive heart failure and chronic renal disease. This case underscores the need for early detection, continuous monitoring, and specialized veterinary care for captive neotropical primates.